2015
DOI: 10.1177/147470491501300111
|View full text |Cite
|
Sign up to set email alerts
|

Personality in Sanctuary-Housed Chimpanzees: A Comparative Approach of Psychobiological and Penta-Factorial Human Models

Abstract: We evaluate a sanctuary chimpanzee sample (N = 11) using two adapted human assessment instruments: the Five-Factor Model (FFM) and Eysenck's PsychoticismExtraversion-Neuroticism (PEN) model. The former has been widely used in studies of animal personality, whereas the latter has never been used to assess chimpanzees. We asked familiar keepers and scientists (N = 28) to rate 38 (FFM) and 12 (PEN) personality items. The personality surveys showed reliability in all of the items for both instruments. These were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 53 publications
1
24
1
Order By: Relevance
“…Curiously, Cattell has never been previously applied in chimpanzees or any other animal species, except humans. Given the success that researches have had in adapting other top‐down rating models (as the Five‐Factor Model: King & Figueredo, ; Eysenck: Ubeda & Llorente, ; Emotions Profile Index: Buirski, Kellerman, Plutchik, Weininger, & Buirski, ; Interpersonal Circumplex: Zeigler‐Hill & Highfill, ), we wanted to examine whether the Cattell 16PF could be employed with nonhuman species as well in order to gain a better understanding of their personalities. Our main goal was to determine whether early life experiences influence personality development using a rapid and innovative tool (Hopper, Cronin, & Ross, ).…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, Cattell has never been previously applied in chimpanzees or any other animal species, except humans. Given the success that researches have had in adapting other top‐down rating models (as the Five‐Factor Model: King & Figueredo, ; Eysenck: Ubeda & Llorente, ; Emotions Profile Index: Buirski, Kellerman, Plutchik, Weininger, & Buirski, ; Interpersonal Circumplex: Zeigler‐Hill & Highfill, ), we wanted to examine whether the Cattell 16PF could be employed with nonhuman species as well in order to gain a better understanding of their personalities. Our main goal was to determine whether early life experiences influence personality development using a rapid and innovative tool (Hopper, Cronin, & Ross, ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, their phylogenetic closeness to humans allows us to better understand and rate their personality traits using questionnaires ( Weiss & Adams, 2013 ). Since one of the most relevant attempts to describe chimpanzee personality using a human model with a hierarchical structure ( King & Figueredo, 1997 ), several studies in captivity and in the wild have shown that chimpanzees have specific personality dimensions or traits that are common to their species ( King, Weiss & Farmer, 2005 ; Weiss et al, 2012 ; Weiss et al, 2017 ), and that questionnaires adapted from human models are reliable measures of their personality ( Freeman et al, 2013 ; Úbeda & Llorente, 2015 ; Weiss & Adams, 2013 ; Weiss et al, 2009 ; Weiss et al, 2017 ). Moreover, several studies have reported correlations between trait rating and observed behavior, both in monkeys ( Ebenau et al, 2019 ; Iwanicki & Lehmann, 2015 ) and in great apes ( Eckardt et al, 2015 ; Murray, 2011 ; Schaefer & Steklis, 2014 ; Vazire et al, 2007 ; Pederson, King & Landau, 2005 ; Konečná et al, 2008 ), thus confirming that personality ratings can successfully predict individual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the HPQ further contains the trait Dominance, which was described for the first time in chimpanzees ( King & Figueredo, 1997 ). More recently, other authors have applied other top-down human models to study chimpanzee personality, such as Eysenck’s Psychoticism-Extraversion-Neuroticism model ( Úbeda & Llorente, 2015 ) or Cattell’s 16 PF ( Ortín et al, 2019 ). The Eysencks’ psychobiological theory ( Eysenck & Eysenck, 1964 ; Eysenck & Eysenck, 1975 ) is focused on the underlying biological mechanisms of personality dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations